Estudio del uso del tiktok como recurso educativo, para desarrollar la creatividad en el área de la educación artística, en los estudiantes de cuarto año de educación general básica de la unidad educativa "F.A.E" de la ciudad de Guaranda, provincia Bolívar, periodo lectivo 2023-2024 - Calvachi Arellano, Norma Jaqueline (2023)
This research project called the use of TikTok to develop creativity in the area of Art Education, was born with the need to provide new teaching strategies that help the educational community to be more creative, create a more dynamic and fun classroom environment. in the area of Art Education through a technological tool. On the other hand, the general objective was to determine the use of this tool as an educational resource and also the specific objectives in order to carry out the proposal that consisted of a guide of activities that help children to be more creative and They have a new way of learning, being the basis for solving the problem. Based on the aforementioned, the methodology used consisted of a mixed approach with the purpose of obtaining data through the application of an interview and survey, in this case to a population of 21 students, as well as the teacher and the parents, which supports the research project. According to the analysis of data obtained from the applied proposal, it was possible to show that the activities applied through TikTok helped to improve the creativity of the educational members, favoring the teaching-learning process. Finally, it is recommended that educational centers implement new forms of teaching and that they include technology tools (TikTok) that make it possible to improve their educational methodology and provide a better environment for students, in addition to getting out of the routine and making education more dynamic and productive.